If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(4x+2)=37-7x
We simplify the equation to the form, which is simple to understand
-4(4x+2)=37-7x
Reorder the terms in parentheses
+(-16x-8)=37-7x
Remove unnecessary parentheses
-16x-8=+37-7x
We move all terms containing x to the left and all other terms to the right.
-16x+7x=+37+8
We simplify left and right side of the equation.
-9x=+45
We divide both sides of the equation by -9 to get x.
x=-5
| 6z-4z+11=7 | | -79-12x=-4x+89 | | -54=16+y | | 2x+6=20+x | | 4x-9=3x+14 | | 0.5x+7=0.75-4 | | -54=15+y | | -26+7x=10x+10 | | [t+9]-8=5 | | 8x+4-2=-5+4x | | x^2+12=-8x | | Y=30+0.85Y+20+40 | | 4/6=238/x | | x+15=-21 | | 5x-52=11x+44 | | 22/16x+50=128 | | -3x-4=8x+7 | | 1/5x-9=-9 | | v=2nr | | 3x+7x-2=6 | | 70+25w=200 | | 1/2y-2/3=7/8 | | 1-4b+2-5b= | | 125=50+.50b | | 12(4/(1/3))=x | | 12m=276 | | 15-7x=18-6x | | x/2+1/4+3/4 | | x=.4+.2y | | 12*(4/1/3)=x | | -0.09m+-22m= | | 6(1-2/3x)=42 |